Sistem Pembuktian pada Hukum Acara Peradilan Tata Usaha Negara di Indonesia - Valencia Prasetyo Ningrum; Rasji Rasji; Yuliya Safitri (Publikasi Indonesia, 2022)
In the midst of an increasingly integrated globalization of communication, the Internet has popularized and shrunk the world while blurring national boundaries with their sovereignty and social order. Technological advances have brought about rapid changes and frontier lifestyle changes in this globalization era. The ratification of the Electronic Information and Transaction Law and the Personal Data Protection Act are new guidelines in the midst of technological advances to support evidence in the procedural law of the State Administrative Court. The existence of State Administrative disputes has implications for the work of State Administrative courts to measure differences of opinion issued by State Administrative bodies or officials with the community when the public interest arises and decisions from the State Administrative agency or officials are deemed detrimental to the interests of the community. In the settlement of state administrative and criminal cases/cases, the judge must examine the evidence submitted by the parties before making a decision or seeking factual and formal truth. Proof is the most important part of the experiment. The purpose of this study is to determine the arrangement of the electronic evidentiary system and its legal force in the State Administrative Court. The research method used in this study is a normative juridical method, namely a legal research method that is carried out by examining library materials or mere secondary materials. The conclusion of this study is the legal force of electronic evidence in the procedural law of the State Administrative Court.